Microbial shelf-life estimation of frozen crispy chicken curry puff under accelerated storage conditions - Rosli, Nur Amira; Mahyudin, Nor Ainy; Mahmud Ab Rashid, Nor-Khaizura; Selamat, Jinap (Malaysian Society for Microbiology, 2024)
Aims: Shelf life estimation, determination, and validation of frozen food are essential in HACCP and can be done by adopting an accelerated shelf life (ASL) study to reduce the time and cost of a long-lasting experiment. This study aims to determine the microbial shelf life of frozen crispy chicken curry puffs (FCCCP). Methodology and results: An ASL study was performed at varying temperatures of -18 ℃, -8 ℃, 2 ℃, and 12 ℃ for 12 weeks. Samples were also maintained at -18 ℃ for 12 months for the actual shelf-life study. Along the studies, microbiological growth (total plate count, yeast and mould count, Salmonella), pH, and moisture content were analysed periodically. Findings from the ASL study indicated that storage at 2 ℃ and 12 ℃ led to an increase in microbiological growth. Yeast and mould count (YMC) had the highest correlation and was used to estimate the shelf life using the Arrhenius equation. The estimated shelf life of FCCCP was 30.5 months at –18 ℃, 6.86 months at –8 ℃, 1.72 months at 2 ℃, and 0.47 months at 12 ℃. The Q10 was 4.45, 3.99, and 3.62 at -18 ℃ to - 8 ℃, -8 ℃ to 2 ℃, and 2 ℃ to 12 ℃, respectively. All samples were within the microbiological limit throughout the storage period in the actual shelf-life study. Salmonella was not detected in any of the studies. Conclusion, significance, and impact of study: These findings provide valuable data for frozen food small and medium enterprises (SMEs) to verify product shelf life during HACCP application. It can serve as a reference in the shelf life determination of frozen foods under inappropriate temperature conditions along the cold chain.